If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(3 + -2X) = 8 + X 6 + (3 * -1 + -2X * -1) = 8 + X 6 + (-3 + 2X) = 8 + X Combine like terms: 6 + -3 = 3 3 + 2X = 8 + X Solving 3 + 2X = 8 + X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 3 + 2X + -1X = 8 + X + -1X Combine like terms: 2X + -1X = 1X 3 + 1X = 8 + X + -1X Combine like terms: X + -1X = 0 3 + 1X = 8 + 0 3 + 1X = 8 Add '-3' to each side of the equation. 3 + -3 + 1X = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 1X = 8 + -3 1X = 8 + -3 Combine like terms: 8 + -3 = 5 1X = 5 Divide each side by '1'. X = 5 Simplifying X = 5
| -9.8-(-1.2)= | | 1.23-(-3.45)= | | 9(-4n-12)= | | 7x+.1+10x-.2=5 | | 3x+y=6forx | | x^4+x^3=4x^2+4x | | -5(-5w+1)= | | 10-6w=-10 | | 3x-(2x+6)=2x-24 | | 8h=40 | | 2(-7v-8)=-86 | | 8B=-5+8B | | 2j=56 | | 25x+-45=180 | | 2(-2c-9)= | | 43=k-14 | | 3+2=-7 | | 7(5k+2)= | | 525+0.21d=585+0.13d | | 8x+3+4x=90 | | X^2-8x+12=24 | | -8(4m-9)= | | y^2=20-x^2 | | 8g-6g=8 | | 2x+1-x=-12 | | -w+173=3 | | 246=193-v | | 233-u=127 | | 49x^8+42x^4+9=f(x) | | 36-3w=w | | 7(6k-4)+3k=-388 | | 4x=5(3) |